MAINTENANCE DAN INSPECTION PADA RUNNER TURBIN - AM Saifutaqi Fatwa Mayfi; Nurul Iman Supardi; Angky Puspawan (UNIB Press, 2022)
The PLTA TES is a generator that relies on water as the driving force for a turbine unit system. There are 7 PLTA Tes turbine units that are still operating with alternating working hours. In keeping a turbine unit operating properly, one way is to do maintenance and general inspection (GI). Maintenance is one way to keep a tool or object from being damaged. Then General Inspection (GI) is a process of activities in the PLTA Test company in checking, measuring, adjusting, repairing and testing one turbine unit in operating for 20,000 hours on a regular basis so that the unit can operate better than before, maintenance is carried out. One of the turbine components that is the object of maintenance is the runner. The runner is the heart of a turbine so that it can operate by relying on flowing water so that the runner can rotate. Runners are given a spot check to see if there is a crack in the runner's condition and measure the runner's clearance so that there is no excessive friction when the runner is operating and the runner is not thirsty.